Influence on soil ecology, tea yield, and quality of tea plant organic cultivation: a mini-review - Liu, Zhiwei; Wang, Qi; Ma, Yan; Zhao, Ming (Frontiers in Agronomy, 2025)
Organic tea cultivation emerges as a pivotal strategy aligning with ecological sustainability and premium agricultural demands. This mini-review summarized the effects of organic cultivation on soil microecology, including raising the pH to the optimal range of 4.5–5.5, increasing soil nutrients, and optimizing enzyme activity and microbial community, thereby increasing the functional components of fresh tea leaves. However, persistent nitrogen limitation under long-term organic planting constrains amino acid synthesis and yield. Critical research frontiers need to focus on (1) organic mineral synergistic regulation technology based on the fertilizer demand pattern of tea plants; (2) ecological network modeling of soil animal insect climate interaction; and (3) analysis of the quality formation mechanism driven by the “Rhizobiont” theory. This review provides a theoretical framework for optimizing carbon and nitrogen cycling in tea gardens and intelligent cultivation of organic tea.